A mode order optimized disk resonator gyroscope considering thermoelastic damping. (15th December 2022) - Qin, Zhengcheng; Ding, Xukai; Ge, Xiao; Ruan, Zhihu; Li, Hongsheng
Abstract: Mode properties and thermoelastic damping (TED) are crucial for the disk resonator gyroscope (DRG). Most of the DRG structure designs do not involve the mode order adjustment and the compatibility design of mode order optimization and quality factor is more lacking. In this paper, a novel mode order optimized DRG is designed and its mode properties and TED are investigated. Parametric studies are conducted to explore the DRG performance which is closely related to structure shapes and dimensions. The parametric study of the proposed DRG indicates that the operation mode being the first order and having a low frequency, the large frequency difference between the operation mode and parasitic modes and the high thermoelastic quality factor are compatible by selecting appropriate structural dimensions. To further improve the quality factor, masses and slots are applied in the proposed DRG respectively. The results show that TED can be effectively reduced with reasonable mass or slot configurations and meanwhile the DRG maintains favorable mode properties due to the strong stability of mode order optimization of the proposed DRG. In general, the research finding in this paper can be a useful reference for other micromachined gyroscope designs. Graphical abstract: Highlights: The proposed disk resonator gyroscope has a mode order optimization function. The compatibility of favorable mode properties and low TED via parametric studies. Adding masses or slots can improve the quality factor but weakens mode properties. The mode order of operation mode is not affected by masses or slots.